Noradrenaline-induced release of newly-synthesized accumbal dopamine: differential role of alpha- and beta-adrenoceptors - Meyer, Francisca; Latour, Judith; Cools, Alexander R.; Verheij, Michel M. M. (Frontiers in Cellular Neuroscience, 2014)
Previous studies have shown that intra-accumbens infusion of isoproterenol (ISO), a beta-adrenoceptor-agonist, and phenylephrine (PE), an alpha-adrenoceptor-agonist, increase the release of accumbal dopamine (DA). In the present study we analyzed whether the ISO-induced release of DA is sensitive to pretreatment with the DA synthesis inhibitor alpha-methyl-para-tyrosine (AMPT). Earlier studies have shown that the PE-induced release of DA is derived from DA pools that are resistant to AMPT. In addition to PE, the alpha-adrenoceptor-antagonist phentolamine (PA) was also found to increase accumbal DA release. Therefore, we investigated whether similar to the DA-increasing effect of PE, the DA increase induced by PA is resistant to AMPT. Pretreatment with AMPT prevented the ISO-induced increase of accumbal DA. The accumbal DA increase after PA was not reduced by the DA synthesis inhibitor, independently of the amount of DA released. These results show that mesolimbic beta-, but not alpha-adrenoceptors, control the release of accumbal newly-synthesized DA pools. The DA-increasing effects of PE have previously been ascribed to stimulation of presynaptic receptors located on noradrenergic terminals, whereas the DA-increasing effects of PA and ISO have been ascribed to an action of these drugs at postsynaptic receptors on dopaminergic terminals. The fact that AMPT did not affect the accumbal DA response to PE and PA, whereas it did prevent the accumbal DA increase to ISO, supports our previously reported hypothesis that the noradrenergic neurons of the nucleus accumbens containing presynaptic alpha-adrenoceptors impinge upon the dopaminergic terminals in the nucleus accumbens containing postsynaptic adrenoceptors of the alpha but not of the beta type. The putative therapeutic effects of noradrenergic agents in the treatment of DA-related disorders are shortly discussed.